Education in adolescence: consequences of lockdown and acceleration - Guilherme, Alexandre Anselmo (2024)
This paper aims to analyze the impact of lockdown on education in the context of social acceleration. In this paper, we address the necessary (re)construction required to enhance the education of adolescents. From this perspective, it examines the potential of the adolescent brain, as advocated by Daniel Siegel. The present study employs a bibliographical research methodology to investigate the impact of social acceleration on education in the aftermath of the lockdown. We emphasize that the adolescent phase is crucial for the development of potentials in the educational context. In this vein, a philosophical analysis of the school is conducted, highlighting it as a space for (re)constructing practices that encourage adolescents to listen to the world around them. Therefore, the school must illuminate the potential of adolescence, such as creativity and openness to novelty, as a space for (re)creating subjects in times of acceleration.